The effect of carbon dioxide, temperature and water stress on growth, yield and seed quality of sunflower (Helianthus Annuus L.) - Kritzinger, Quenton (University of Pretoria, 2024)
Dissertation (MSc Agric (Agronomy))--University of Pretoria, 2024.